The dialectical image as the critical inner mirror - Rybínski, Lukasz K. (Aktualitet - Litteratur, kultur og medier, 2015)
Lukasz K. Rybínski, Faculty of Philosophy, University of Gdansk: "The dialectical image as the critical inner mirror"